I am wondering if the sum $$S=\sum_{k=1}^{\infty}\frac{1}{k(3k-1)}$$ has an exact expression. And when I plugged it into Wolfram Alpha it spitted out: $$S=\frac{1}{6}\Big(-\sqrt{3} π + 9 \ln(3)\Big)$$ I am wondering how is the answer obtained? Is there a simple way of not using math beyond second year university to arrive to that answer?

  • $\begingroup$ There is a typo. k instead of x $\endgroup$ – HAMIDINE SOUMARE Apr 12 at 23:11

$$\frac{1}{1-x}=\sum_{k=0}^{\infty}x^k$$ $$\frac{1}{1-x}=\sum_{k=1}^{\infty}x^{k-1}$$ $$\int_{0}^{x}\frac{1}{1-x}dx=\int_{0}^{x}\sum_{k=1}^{\infty}x^{k-1}dx$$ $$-\log(1-x)=\sum_{k=1}^{\infty}\frac{x^{k}}{k}$$ let $x\rightarrow x^3$ $$-\log(1-x^3)=\sum_{k=1}^{\infty}\frac{x^{3k}}{k}$$ $$\frac{-1}{x^2}\log(1-x^3)=\sum_{k=1}^{\infty}\frac{x^{3k-2}}{k}$$

$$\int_{0}^{1}\frac{-1}{x^2}\log(1-x^3)dx=\int_{0}^{1}\sum_{k=1}^{\infty}\frac{x^{3k-2}}{k}dx$$ $$\frac{1}{6} (- \sqrt{3} π + 9 \log(3))=\sum_{k=1}^{\infty}\frac{1}{k(3k-1)}$$

  • 1
    $\begingroup$ I was thinking of something similar, only taking an appropriate combination of $\log(1-x), \log(1-\zeta x), \log(1-\zeta^2 x)$ with $\zeta = e^{2\pi i/3}$ to get the right coefficients of $\frac{1}{3}$ for $\frac{x^{3k-1}}{3k-1}$ and $-\frac{1}{3}$ for $\frac{x^{3k}}{3k}$. $\endgroup$ – Daniel Schepler Apr 13 at 0:05

First, lets transform the sum into


Using a method given here, this becomes

$$=\frac{1}{3}\left(3H\left(0\right)-3H\left(-\frac{1}{3}\right) \right)$$

(where $H(x)$ denotes the $x$th harmonic number). This simplifies down to


(as the $0$th harmonic number is $0$). Now, there is a certain relationship between the generalized harmonic numbers and the digamma function. That is


(where $\gamma$ is the Euler-Mascheroni constant). Thus, our value becomes


Getting to the punchline finally, we can use Gauss's Digamma Theorem to get

$$=-\gamma+\gamma+\log(2\cdot 3)+\frac{\pi}{2}\cot\left(\frac{2}{3}\pi \right)-2\cos\left(\frac{2\cdot 2}{3}\pi \right)\log\left[\sin\left(\frac{1}{3}\pi\right)\right]$$


$$= \log(2)+\log(3)-\frac{\sqrt{3}\pi}{6}+\frac{1}{2}\log\left(3\right)-\log(2)$$

$$= -\frac{\sqrt{3}\pi}{6}+\frac{3}{2}\log\left(3\right)=\frac{1}{6}\left(-\sqrt{3}\pi+9\log(3)\right).$$

I'm not sure if this qualifies as a simple way of obtaining the answer, but I'm can't think of anything easier.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.